HAMUTU PELAYANAN JAMPERSAL DI PUSKESMAS KOTA YOGYAKARTA - , UMI NUR CHARIYATI; , dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background:Jampersal (Jaminan Persalinan) is a groundbreaking effort to facilitate access to service delivery, so as to reduce the Infant Mortality Rate (IMR) and Maternal Mortality Rate (MMR). The impact of the program is increased patient visits Jampersal ANC (Ante Natal Care) and maternity delivery in health centers, which certainly will affect the quality of service. One of management activities to improve the quality of service is to carry out supervision, where the implementation is sometimes not priority. This study examines how Jampersal service quality and supervision efforts by both the public health care and Health District to improve the quality of service in Jampersal. Methods: This research is descriptive study with qualitative research and case study design. This study was conducted in Mergangsan health center Yogyakarta city. Colecting data through in-depth interviews to participants Jampersal, midwives, midwives coordinators, Head of public health care, head of UPT PJKD, Head of Family Halth Section and Head of Health Service Department in Yogyakarta Health District. To complete the data, the syudy observation and tracking documents. Results: Patients of Jampersal got all kind of services in accordance with the Minimum Service Standards (MSS) examination of pregnancy until the birth process in comprehensive manner. Patients are quite satisfied to obtain the service pack, but were less satisfied in the long process of consultation and the ANC. Referral mechanisms for patients of Jampersal relatively easily and quickly, only hampered by policies that restrict private hospital receives patients of Jampersal. Midwives workload increases because of skyrocketing patients as well s the adinistrative woekload and assignment of Jampersal socialization, while receiving incentives are not comparable with the workload. Health District has not effectively supervise the Jampersal services in health centers, because there is no organization and policy support activities adequate for supervising the implementation. Conclusion: Although supervision is problem solving and yet not give effect to an increase in motivation and performance officer, a supervisor already has responsibility for supervision fee regardless of the presence or absence of supervision.